Analysing the Robustness of Spice Chains in Nepal from a Smallholder Perspective - Bhattarai, Salil; Lyne, Michael C; Martin, Sandra K (Asian Journal of Agriculture and Rural Development, 2015)
This study assesses the performance of supply chains for ginger and large cardamom, two major export crops produced in Nepal. In particular, it aims to identify factors that constrain marketing choices available to smallholders, so limiting the chain’s robustness from their perspective. A qualitative case study method was used to gather and analyse data on farmer-buyer dyads in the ginger and cardamom chains. These case studies were informed by a conceptual model based on Transaction Cost Economics. The analysis included a cross-case comparison to identify the effects of external attributes on the modes of engagement available to smallholders. Informal market trading was the only mode of smallholder engagement observed in both chains. However, there was evidence that smallholders had previously engaged in relational contracts in the ginger chain, and in ‘captive’ relational contracts in the cardamom chain. The analysis suggests that access to other modes of engagement is constrained mainly by under-investment in value-adding assets. Traditional cooperatives can and do help to resolve problems of asymmetric information and high unit transaction costs, but more innovative cooperative models are required to encourage the investment needed to finance value-adding assets and activities.